Shape-controllable graphdiyne-like two-dimensional metal organic framework material as well as preparation method and application thereof
By using functionalized hydroxyl ligands to coordinate reactions with transition metal ions under solvothermal conditions and surfactants to regulate crystal growth, a graphiteyne-like two-dimensional metal organic framework material was prepared, which solved the traditional The crystallinity and morphological structure limitations of 2D-MOF in photocatalytic applications achieve efficient photocatalytic performance.
Patent Information
- Application Number
- CN202411407115.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-10
AI Technical Summary
Traditional two-dimensional metal organic frame materials (2D-MOFs) are limited by crystallinity and morphological structure in photocatalytic applications, making it difficult to achieve efficient photocatalytic performance.
By using -C≡C-C≡C-functionalized hydroxyl ligand with transition metal ions under solvothermal conditions, and surfactant regulates crystal growth, a graphite-like two-dimensional morphology is prepared by using surfactant to regulate crystal growth. Metal organic frame materials form high crystallinity and highly conjugated structures to promote photocatalytic reactions.
Achieve efficient photocatalytic activity, especially in photogenerating exciton migration and charge transfer, the photocatalytic hydrogen production performance is improved. Materials with different morphology have different catalytic properties, and the hollow tube morphology shows the highest light Catalytic hydrogen production rate.
Smart Images

Figure CN119285972A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of metal organic framework functional materials, and specifically relates to a morphology-controllable graphyne-like two-dimensional metal organic framework material, and a preparation method and application thereof. Background Art
[0002] Due to the extensive use of fossil fuels in modern industry, ecological environmental problems and energy crisis have attracted great attention. Solar energy is a clean, safe, inexhaustible and inexhaustible energy source, so using solar energy to replace fossil fuels and reduce exhaust emissions has become a promising strategy. So far, some technologies have been reported to convert solar energy into electrical energy, thermal energy and chemical energy.
[0003] Since Fujishima first reported TiO2 as a semiconductor for photocatalytic water splitting to produce hydrogen in 1972, photocatalytic hydrogen production from water has aroused strong interest due to its following advantages: 1) Water is the most abundant and cleanest resource on earth; 2) Hydrogen will be regenerated into water after combustion, which can provide high energy and is environmentally friendly; 3) The widespread use of hydrogen energy will establish a simple and efficient energy cycle in the presence of sunlight and appropriate catalysts for the sustainable development of earth civilization. However, finding efficient catalysts for photocatalytic water splitting is a key factor. Commonly used heterogeneous semiconductor catalysts in photocatalytic hydrogen production include TiO2, CdS, BiVO4, Ta3N5, g-C3N4, etc., but the inherent defects of inorganic semiconductors themselves lead to relatively limited photocatalytic performance.
[0004] Metal-organic framework compounds (MOFs) are porous crystalline materials with an open network structure formed by metal centers and multidentate organic ligands through coordination bonds. Compared with traditional porous materials (such as zeolites, mesoporous silica and activated carbon), MOFs have unique advantages such as high porosity, large specific surface area, clear structure and high adjustability. They have attracted the attention and research of many scientists in the fields of adsorption, separation, magnetism, hydrogen storage, catalysis, capacitors and molecular recognition. In recent years, MOFs and their derivatives have attracted much attention in the application of photoelectrochemical energy conversion due to their unique structure and physicochemical properties.
[0005] However, the limited active sites of traditional MOFs inevitably restrict their application in photocatalysis. Two-dimensional metal-organic frameworks (2D-MOFs) are composed of conjugated organic ligands containing multidentate ortho-substituted functional groups (such as -NH2, -OH, -SH or -SeH) and transition metal ions (such as Cu 2+ 、Co 2+ 、Ni 2+) coordinate on a two-dimensional plane to form a network structure with π-d conjugation, promoting strong in-plane conjugation and weak out-of-plane π-π stacking interactions, thereby providing an effective electron transfer path. 2D-MOF has a high surface-to-volume atomic ratio and abundant surface modification sites, which helps to reduce diffusion barriers, promote the contact between reactants and active sites, and accelerate mass transfer and charge transfer. However, the crystallinity and morphology of 2D-MOF play a key role in its electrochemical performance. At present, the preparation of highly crystalline 2D-MOF with controllable morphology and rich functions is still facing challenges. Summary of the invention
[0006] Based on the above reasons, the first purpose of the present invention is to provide a method for preparing a morphology-controllable graphyne-like two-dimensional metal-organic framework material, in which a -C≡CC≡C-functionalized hydroxyl ligand is coordinated with a copper salt under solvent thermal conditions, and the crystal growth is regulated by a surfactant to obtain a morphology-controllable graphyne-like two-dimensional metal-organic framework material that exhibits excellent photocatalytic activity.
[0007] The second purpose of the present invention is to provide a morphology-controllable graphyne-like two-dimensional metal-organic framework material, which has a highly crystalline, highly conjugated graphyne-like two-dimensional metal-organic framework structure formed by the coordination of hydroxyl ligands, diyne groups and metal atoms; promotes d-π orbital hybridization between hydroxyl ligands and transition metal ions to improve its photocatalytic performance.
[0008] The third object of the present invention is to provide a morphology-controllable graphyne-like two-dimensional metal-organic framework material for use as a catalyst for photocatalytic reactions.
[0009] The first object of the present invention can be achieved by adopting the following technical solutions:
[0010] A method for preparing a morphology-controllable graphyne-like two-dimensional metal-organic framework material, wherein a monomer having a structure shown in formula I is subjected to a solvothermal reaction with a transition metal ion precursor to obtain a morphology-controllable graphyne-like two-dimensional metal-organic framework material having a structure unit shown in formula II;
[0011]
[0012] Furthermore, the transition metal ion precursor is Cu 2+ 、Co 2+ 、Ni 2+ Ionic acetic acid, hydrochloric acid, sulfuric acid or nitric acid compounds and their hydrates.
[0013] Furthermore, the solvent thermal reaction is carried out in the presence of a quaternary ammonium salt surfactant; the mass ratio of the quaternary ammonium salt surfactant to the monomer of the structure shown in Formula I is (2-4):1.
[0014] Furthermore, the quaternary ammonium salt surfactant is hexadecyltrimethylammonium bromide; the mass ratio of hexadecyltrimethylammonium bromide to the monomer of the structure shown in Formula I is 2:1 or 4:1.
[0015] Furthermore, the molar ratio of the monomer of the structure shown in Formula I to the transition metal ion precursor is 1:(1.2-2.0).
[0016] Further, the conditions of the solvothermal reaction are:
[0017] The reaction solvent is a mixed solvent of DMF and water, wherein the volume ratio of DMF to water is (5-20):1;
[0018] The molar volume ratio of the monomer of the structure shown in Formula I to the solvent is 1 μmol:(50-200) mL;
[0019] The reaction temperature is 70-100°C; the reaction time is 6-144h.
[0020] Furthermore, the reaction includes a separation and washing process; after separation, the solid is washed with DMF and acetone, and the solid is Soxhlet extracted in acetone for 1-5 days.
[0021] The second object of the present invention can be achieved by adopting the following technical solutions:
[0022] A morphology-controllable graphyne-like two-dimensional metal-organic framework material is prepared by any of the above-mentioned methods for preparing a morphology-controllable graphyne-like two-dimensional metal-organic framework material.
[0023] Furthermore, the graphyne-like two-dimensional metal-organic framework material has a size of 1-20 μm and is a solid hexagonal prism, a hexagonal sheet structure or a hexagonal hollow tube structure.
[0024] The third object of the present invention can be achieved by adopting the following technical solutions:
[0025] The above-mentioned morphology-controllable graphyne-like two-dimensional metal-organic framework material is used as a catalyst for photocatalytic hydrogen production reaction.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. A method for preparing a morphology-controllable graphyne-like two-dimensional metal-organic framework material of the present invention, wherein -C≡CC≡C-functionalized hydroxyl ligands react with transition metal ions under solvent thermal conditions to form a highly crystalline, highly conjugated graphyne-like two-dimensional MOF.
[0028] 2. The method for preparing a morphology-controllable graphyne-like two-dimensional metal-organic framework material of the present invention utilizes the surfactant CTAB and adjusts the growth conditions of MOF, such as the ratio of reactants, concentration, temperature, time, etc. to obtain a morphology-controllable graphyne-like two-dimensional metal-organic framework material having good photocatalytic activity.
[0029] 3. The present invention provides a morphology-controllable graphyne-like two-dimensional metal-organic framework material, which has abundant embedded acetylene as promising active sites to assist the migration of photogenerated excitons, thereby potentially improving the performance of photocatalytic hydrogen production; in addition, the metal-organic framework material has a controlled morphology of solid hexagonal prisms, hexagonal sheet structures or hexagonal hollow tube structures; it has a high surface-to-volume atomic ratio and abundant surface modification sites, which helps to reduce diffusion barriers, promote the contact between reactants and active sites, accelerate mass transfer and charge transfer, and further improve the performance of photocatalytic hydrogen production. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Single crystal X-ray structure simulation was performed for Cu-L prepared in Example 2;
[0031] Figure 2 The simulated structure diagram of Cu-L AA stacking;
[0032] Figure 3 Scanning electron microscope (SEM) images of Cu-L prepared in Example 2 and Cu-L-bulk prepared in Examples 3 to 5;
[0033] Figure 4 This is a scanning electron microscope (SEM) image of the Cu-L-hollow prepared in Example 6;
[0034] Figure 5 The ultraviolet absorption spectrum of Cu-L prepared in Example 2;
[0035] Figure 6 Mott-Schottky spectrum of Cu-L prepared in Example 2;
[0036] Figure 7 The photocatalytic hydrogen evolution rate diagram under different catalysts;
[0037] Figure 8 This is a molecular structure diagram of the morphology-controllable graphyne-like two-dimensional metal-organic framework material of the present invention. DETAILED DESCRIPTION
[0038] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only partial embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0039] As catalysts, MOFs have the following remarkable characteristics: (1) highly ordered porous structure, uniform pore size distribution, and large specific surface area, which are conducive to the dispersion of active components and provide a large number of active sites for catalytic reactions; (2) pore size controllability: by adjusting the metal center and organic ligand, MOFs materials with pore sizes ranging from ultramicropores to mesopores can be obtained, which is conducive to the preparation of complex porous catalysts; (3) easy functionalization, which is conducive to the combination of MOFs with other functional substances to prepare composite materials and improve the catalytic performance of MOFs themselves; (4) metal nodes are adjustable, and by changing the type of metal ions, the activity of MOFs catalysts can be improved while maintaining their original topological structure. However, the crystallinity and morphology of 2D c-MOF affect and restrict its photocatalytic performance. At present, there is a lack of preparation methods for morphology-controllable two-dimensional conjugated MOFs, which limits its application in photocatalysis.
[0040] Based on the above content, the present application provides a morphology-controllable graphyne-like two-dimensional metal-organic framework material and its preparation method and application.
[0041] A method for preparing a morphology-controllable Graphyne-like two-dimensional metal-organic framework material, wherein a monomer having a structure shown in formula I is subjected to a solvothermal reaction with a transition metal ion precursor to obtain a morphology-controllable Graphyne-like two-dimensional metal-organic framework material having a structure unit shown in formula II; Figure 8 shown.
[0042]
[0043] The monomer I of the structure shown in formula I, the -C≡CC≡C-functionalized hydroxyl ligand, reacts with transition metal ions under solvothermal conditions, wherein the hydroxyl groups are coordinated and connected with the transition metal ions, and the monomers of the structure shown in formula I are connected into the structural units shown in formula II, thereby forming a highly crystalline and highly conjugated graphyne-like two-dimensional MOF. The -C≡CC≡C-group in the monomer of the structure shown in formula I contains abundant embedded acetylene as promising active sites to assist the migration of photogenerated excitons, thereby potentially improving the performance of photocatalytic hydrogen production. In addition, the π orbital of the diacetylene group of the monomer of the structure shown in formula I and the π orbital of the benzene ring constitute a conjugated system, which can enhance the energy band dispersion and promote the maximization of electron delocalization, further promote the d-π orbital hybridization of the hydroxyl ligand and the transition metal ion, and improve its photocatalytic performance. Combined with the high surface-to-volume atomic ratio and abundant surface modification sites of 2D-MOF itself, the diffusion barrier is reduced, the contact between the reactants and the active sites is promoted, the mass transfer and charge transfer are accelerated, and the performance of photocatalytic hydrogen production is comprehensively improved.
[0044] As one embodiment, the transition metal ion precursor is Cu 2+ 、Co 2+ 、Ni 2+ ions of acetic acid, hydrochloric acid, sulfuric acid or nitric acid compounds and their hydrates. Copper, cobalt and nickel are transition metals with excellent catalytic properties. Their metal ions can coordinate with hydroxyl oxygen, so they can be used as connection sites to connect the structural monomers shown in formula I to form a two-dimensional MOF. Preferably, the transition metal ion is Cu 2+ ions, and the transition metal ion precursor is copper acetate.
[0045] As one embodiment, the solvothermal reaction is carried out in the presence of a quaternary ammonium surfactant. Preferably, the quaternary ammonium surfactant is hexadecyltrimethylammonium bromide (CTAB). The addition of the surfactant, wherein the cationic properties and rich long-chain alkyl chains of the quaternary ammonium salt can regulate the growth and structure formation of the MOF.
[0046] As one embodiment, the mass ratio of the quaternary ammonium salt surfactant to the monomer of the structure shown in Formula I is (2-4): 1. Further, the mass ratio of hexadecyltrimethylammonium bromide to the monomer of the structure shown in Formula I is 2: 1 or 4: 1. The amount of quaternary ammonium salt surfactant added affects the size of the MOF crystals formed. Generally speaking, the addition of quaternary ammonium salt surfactants will grow MOF crystals with severe accumulation and different sizes into micrometer-scale hexagonal prisms or hexagonal flakes, and as the content of quaternary ammonium salt surfactant increases, the size of the crystals is further increased.
[0047] As one embodiment, the molar ratio of the monomer of the structure shown in Formula I to the transition metal ion precursor is 1:(1.2-2.0). One transition metal ion is coordinated with two hydroxyl oxygens on one phenyl group of two monomers of the structure shown in Formula I, and a monomer of the structure shown in Formula I has a total of three phenyl groups connected to hydroxyl groups. Therefore, the molar ratio of the monomer of the structure shown in Formula I to the transition metal ion precursor is 1:(1.2-2.0), which can ensure the formation of MOF structural materials.
[0048] As one embodiment thereof, the conditions for the solvothermal reaction are:
[0049] The reaction solvent is a mixed solvent of DMF and water, and the volume ratio of DMF to water is (5-20):1.
[0050] As one embodiment, the molar volume ratio of the monomer of the structure shown in Formula I to the solvent is 1 μmol:(50-200) mL.
[0051] As one embodiment, the reaction temperature is 70-100°C and the reaction time is 6-144h. The length of the reaction time also has a certain influence on the MOF structure. In this embodiment, under the same CTAB content, as the reaction time increases, the size of the MOF material gradually increases, and after the reaction time reaches a certain length, the structure of the MOF material undergoes a significant change.
[0052] As one of the embodiments, the reaction time is within 4 days, and the morphology-controllable graphyne-like two-dimensional metal-organic framework material is a solid hexagonal prism or hexagonal sheet structure.
[0053] As one implementation mode, the reaction time is 4 to 6 days, and the morphology-controllable graphyne-like two-dimensional metal-organic framework material is a hexagonal hollow tube structure.
[0054] As one embodiment, the reaction includes a separation and washing process; after separation, the solid is washed with DMF and acetone, and the solid is subjected to Soxhlet extraction in acetone for 1-5 days.
[0055] As one embodiment, the monomer of the structure shown in Formula I is prepared by the following reaction path:
[0056]
[0057] The present invention also provides a morphology-controllable graphyne-like two-dimensional metal-organic framework material, which is prepared by any of the above-mentioned methods for preparing a morphology-controllable graphyne-like two-dimensional metal-organic framework material.
[0058] As one embodiment, the 2D Graphyne-like Metal-Organic Framework material has a size of 1-20 μm; it is a solid hexagonal prism, a hexagonal sheet structure or a hexagonal hollow tube structure. By using the surfactant CTAB and adjusting the growth conditions of the MOF: reactant ratio, concentration, temperature, time, etc., a morphology-controllable Graphyne-like 2D Metal-Organic Framework material is obtained, which is a hexagonal prism or hollow tube MOF with controllable size and morphology, and has potential photocatalytic activity.
[0059] The present invention also provides a morphology-controllable graphyne-like two-dimensional metal organic framework material for use as a catalyst for photocatalytic hydrogen production reaction.
[0060] As one embodiment, the photocatalytic reaction is carried out in a solution of DMF and water as a reaction liquid, 1,3-dimethylbenzimidazole (BIH) is used as a sacrificial agent, chloroplatinic acid is used as a co-catalyst, and tris(2,2-bipyridine)ruthenium chloride is used as a photosensitizer.
[0061] The following is a further description with reference to specific embodiments.
[0062] Example 1
[0063] 0.01 μmol of the monomer of the structure shown in Formula I and 0.01 μmol of cobalt acetate were weighed into a glass tube (8×150 mm), 0.42 ml of N,N-dimethylformamide and 0.08 mL of water were added, and the mixture was then ultrasonically treated for 10 min; the glass tube was sealed with an oxyhydrogen flame and heated in an oven at 70°C for 24 h, and then naturally cooled to room temperature; the crystals were collected by filtration, the sample was washed with DMF (5 mL×5) and acetone (5 mL×5), and then Soxhlet extracted in acetone solution for 3 days and dried in vacuum to obtain a morphology-controllable graphyne-like two-dimensional metal-organic framework material, named Cu-L.
[0064] Example 2
[0065] 0.01 μmol of the monomer of the structure shown in formula I and 0.016 μmol of Cu(NO3)2·3H2O were weighed into a glass tube (8×150 mm), 1 ml of N,N-dimethylformamide and 0.1 mL of water were added, and the mixture was then ultrasonically treated for 10 min; the glass tube was sealed with an oxyhydrogen flame and heated in an oven at 85°C for 48 h, and then naturally cooled to room temperature; the crystals were collected by filtration, the sample was washed with DMF (5 mL×5) and acetone (5 mL×5), and then Soxhlet extracted in acetone solution for 3 days and dried in vacuum to obtain a morphology-controllable graphyne-like two-dimensional metal-organic framework material, named Cu-L.
[0066] Example 3
[0067] 0.01 μmol of the monomer of the structure shown in formula I and 0.016 μmol of Cu(NO3)2·3H2O were weighed into a glass tube (8×150 mm), 1 ml of N,N-dimethylformamide and 0.1 mL of water were added, and then 10 mg of CTAB was added, and then the mixture was ultrasonically treated for 10 min; the glass tube was sealed with an oxyhydrogen flame and heated in an oven at 85°C for 48 h, and then naturally cooled to room temperature; the crystals were collected by filtration, the sample was washed with DMF (5 mL×5) and acetone (5 mL×5), and then Soxhlet extracted in acetone solution for 3 days and dried in vacuum to obtain a morphology-controllable graphyne-like two-dimensional metal-organic framework material, named Cu-L-bulk.
[0068] Example 4
[0069] 0.01 μmol of the monomer of the structure shown in formula I and 0.016 μmol of Cu(NO3)2·3H2O were weighed into a glass tube (8×150 mm), 1 ml of N,N-dimethylformamide and 0.1 mL of water were added, and then 20 mg of CTAB was added, and then the mixture was ultrasonically treated for 10 min; the glass tube was sealed with an oxyhydrogen flame and heated in an oven at 85°C for 48 h, and then naturally cooled to room temperature; the crystals were collected by filtration, the sample was washed with DMF (5 mL×5) and acetone (5 mL×5), and then Soxhlet extracted in acetone solution for 3 days and dried in vacuum to obtain a morphology-controllable graphyne-like two-dimensional metal-organic framework material, named Cu-L-bulk.
[0070] Example 5
[0071] 0.01 μmol of the monomer of the structure shown in formula I and 0.016 μmol of Cu(NO3)2·3H2O were weighed into a glass tube (8×150 mm), 1 ml of N,N-dimethylformamide and 0.1 mL of water were added, and then 20 mg of CTAB was added, and then the mixture was ultrasonically treated for 10 min; the glass tube was sealed with an oxyhydrogen flame and heated in an oven at 85°C for 72 h, and then naturally cooled to room temperature; the crystals were collected by filtration, the sample was washed with DMF (5 mL×5) and acetone (5 mL×5), and then Soxhlet extracted in acetone solution for 3 days and dried in vacuum to obtain a morphology-controllable graphyne-like two-dimensional metal-organic framework material, named Cu-L-bulk.
[0072] Example 6
[0073] 0.01 μmol of the monomer of the structure shown in formula I and 0.016 μmol of Cu(NO3)2·3H2O were weighed into a glass tube (8×150 mm), 1 ml of N,N-dimethylformamide and 0.1 mL of water were added, and then 20 mg of CTAB was added, and then the mixture was ultrasonically treated for 10 min; the glass tube was sealed with an oxyhydrogen flame and heated in an oven at 85°C for 96 h, and then naturally cooled to room temperature; the crystals were collected by filtration, the sample was washed with DMF (5 mL×5) and acetone (5 mL×5), and then Soxhlet extracted in acetone solution for 3 days and dried in vacuum to obtain a morphology-controllable graphyne-like two-dimensional metal-organic framework material, named Cu-L-hollow.
[0074] Example 7
[0075] 0.01 μmol of the monomer of the structure shown in formula I and 0.012 μmol of NiCl2·6H2O were weighed into a glass tube (8×150 mm), 1.9 ml of N,N-dimethylformamide and 0.1 mL of water were added, and then 20 mg of CTAB was added, and then the mixture was ultrasonically treated for 10 min; the glass tube was sealed with an oxyhydrogen flame and heated in an oven at 100°C for 144 h, and then naturally cooled to room temperature; the crystals were collected by filtration, the sample was washed with DMF (5 mL×5) and acetone (5 mL×5), and then Soxhlet extracted in an acetone solution for 3 days and dried in a vacuum to obtain a morphology-controllable graphyne-like two-dimensional metal-organic framework material, named Cu-L-hollow.
[0076] Test example:
[0077] (1) Single crystal X-ray structure simulation was performed on Cu-L prepared in Example 2; the single crystal structure is as follows Figure 1 As shown in the figure, before activation is before Soxhlet extraction, and after activation is after Soxhlet extraction. The simulated structure of Cu-L AA stacking is shown in Figure 2 shown.
[0078] from Figure 1 From the results of the single crystal X-ray diffraction test, it can be seen that the diffraction spectrum of the synthesized Cu-L is highly consistent with the X-ray powder diffraction of the AA stacking structure simulated by the MaterialsStudio software in terms of peak position, indicating that the synthesized Cu-L is a two-dimensional layered structure of AA stacking. Moreover, it can be seen from the diffraction spectrum that the diffraction peak of Cu-L is very strong and sharp, indicating that the synthesized metal organic framework Cu-L has a high degree of crystallinity.
[0079] (2) The Cu-L prepared in Example 2, the Cu-L-bulk prepared in Examples 3 to 5, and the Cu-L-hollow prepared in Example 6 were observed by scanning electron microscope (SEM). Figure 3 and Figure 4 As shown, Figure 3 a is Cu-L of Example 2; Figure 3 b is the Cu-L-bulk prepared in Example 3; Figure 3 c is the Cu-L-bulk prepared in Example 4; Figure 3 d is the Cu-L-bulk prepared in Example 5; Figure 4 This is the Cu-L-hollow prepared in Example 6.
[0080] from Figure 3 It can be seen that in Example 2, no CTAB is added, and the prepared Cu-L is severely stacked and in block form. After adding CTAB to Example 3, Example 4 and Example 5, the morphology with severe stacking and uneven size is changed to Cu-L-bulk with better crystallinity that can grow micron-level hexagonal prisms or hexagonal flake morphology; and as the amount of CTAB added in Example 3 and Example 4 increases from 10 mg to 20 mg, the size of Cu-L-bulk increases from 1-5 μm to 5-10 μm. It can be seen from Example 4 and Example 5 that under the same amount of CTAB added, the time of the hydrothermal reaction increases from 2 days to 3 days, and the size of Cu-L-bulk also increases accordingly, from 5-10 μm to 10-20 μm. In particular, when the time of the hydrothermal reaction is further increased to more than 4 days, a hexagonal hollow tube structure, Cu-L-hollow, can be obtained. This illustrates the controllability of morphology by CTAB and reaction time.
[0081] (3) The Cu-L prepared in Example 2 was subjected to a solid UV-visible light absorption test, and the semiconductor band gap was tested and a Mott-Schottky spectrum was obtained. The UV absorption spectrum was as follows: Figure 5 As shown; the Mott-Schottky spectrum is as Figure 6 shown.
[0082] from Figure 5 The absorption spectrum test results show that Cu-L exhibits a wide absorption spectrum of 200-2500nm covering the visible light and near-infrared light range, greatly enhancing the absorption of sunlight. And its Eg is 2.75eV, with a large bandgap width, which makes the electron-hole have a strong redox ability.
[0083] from Figure 6 From the Mott-Schottky spectrum, it can be seen that the flat band potential of Cu-L is 0.29 V, which shows that Cu-L has good light absorption ability and potential photocatalytic hydrogen production ability.
[0084] Test example:
[0085] In order to study the photocatalytic hydrogen production performance of morphology-controllable Graphyne-like two-dimensional metal-organic framework materials, 3 mg powder samples of Cu-L, Cu-L-bulk, and Cu-L-hollow were dispersed in 2.5 mL DMF and 2.5 mL deionized water as photocatalysts, and a certain amount of 1,3-dimethylbenzimidazole (BIH) was added as a sacrificial agent and a quantitative amount of chloroplatinic acid as a co-catalyst, and tris(2,2-bipyridyl)ruthenium chloride was used as a photosensitizer. The system was closed after passing argon for 30 minutes. LED lamp was used as a visible light source, and the sample was manually injected after 3 hours of photocatalytic experiment. The gas integrated area was determined by gas chromatography.
[0086] In the conditions of 2.5 mL DMF, 2.5 mL H2O, 3 mg tris(2,2-bipyridyl)ruthenium chloride, 5 mg BIH, and 20 ul chloroplatinic acid aqueous solution (5 mg / mL), the photocatalytic hydrogen production rates (HER) of Cu-L, Cu-L-bulk, and Cu-L-hollow are as follows: Figure 7 shown.
[0087] from Figure 7 It can be seen that the photocatalytic hydrogen production (HER) of Cu-L is 404 μmol g -1 h -1 ; Cu-L-bulk photocatalytic hydrogen production (HER) is 544 μmol g -1 h -1 ; Cu-L-hollow photocatalytic hydrogen production (HER) is 885 μmol g -1 h -1 It is shown that the morphology-controllable graphyne-like two-dimensional metal-organic framework material of the present application has good HER performance, and among them, Cu-L-hollow has the best HER performance because of its higher specific surface area and more exposed active sites.
[0088] In summary, the morphology-controllable Graphyne-like two-dimensional metal-organic framework material of the present invention, -C≡CC≡C-functionalized hydroxyl ligands and transition metal ion precursors undergo coordination reaction under solvent thermal conditions to form highly crystalline, highly conjugated Graphyne-like two-dimensional MOF. The conjugated system formed by the π orbital of the alkynyl group and the π orbital of the benzene ring can not only enhance the band dispersion, but also maximize the electron delocalization, promote the hydroxyl ligands and transition metal ions to carry out d-π orbital hybridization, and improve their catalytic performance. At the same time, by using the surfactant CTAB and adjusting the growth conditions of MOF (reactant ratio, concentration, temperature, time, etc.), a morphology-controllable Graphyne-like two-dimensional metal-organic framework material is obtained, and different morphologies have different HER performances, and the hollow tube shape has the highest HER performance.
[0089] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.
Claims
1. A method for preparing a morphology-controllable graphyne-like two-dimensional metal-organic framework material, characterized in that: The monomer of the structure shown in formula I is subjected to a solvothermal reaction with a transition metal ion precursor to obtain a morphology-controllable graphyne-like two-dimensional metal-organic framework material of the structural unit shown in formula II; 2. The method for preparing a morphology-controllable graphyne-like two-dimensional metal-organic framework material according to claim 1, characterized in that: The transition metal ion precursor is Cu 2+ 、Co 2+ 、Ni 2+ Ionic acetic acid, hydrochloric acid, sulfuric acid or nitric acid compounds and their hydrates.
3. The method for preparing a morphology-controllable graphyne-like two-dimensional metal-organic framework material according to claim 1, characterized in that: The solvent thermal reaction is carried out in the presence of a quaternary ammonium salt surfactant; the mass ratio of the quaternary ammonium salt surfactant to the monomer of the structure shown in formula I is (2-4):
1.
4. The method for preparing a morphology-controllable graphyne-like two-dimensional metal-organic framework material according to claim 3, characterized in that: The quaternary ammonium salt surfactant is hexadecyltrimethylammonium bromide; the mass ratio of hexadecyltrimethylammonium bromide to the monomer of the structure shown in formula I is 2:1 or 4:
1.
5. The method for preparing a morphology-controllable graphyne-like two-dimensional metal-organic framework material according to claim 1, characterized in that: The molar ratio of the monomer of the structure shown in Formula I to the transition metal ion precursor is 1:(1.2-2.0).
6. The method for preparing a morphology-controllable graphyne-like two-dimensional metal-organic framework material according to claim 1, characterized in that: The conditions for the solvothermal reaction are: The reaction solvent is a mixed solvent of DMF and water, wherein the volume ratio of DMF to water is (5-20):1; The molar volume ratio of the monomer of the structure shown in Formula I to the solvent is 1 μmol:(50-200) mL; The reaction temperature is 70-100°C; the reaction time is 6-144h.
7. The method for preparing a morphology-controllable graphyne-like two-dimensional metal-organic framework material according to claim 1, characterized in that: The reaction comprises a separation and washing process; after separation, the solid is washed with DMF and acetone, and the solid is subjected to Soxhlet extraction in acetone for 1-5 days.
8. A morphology-controllable graphyne-like two-dimensional metal-organic framework material, characterized in that: The material is prepared by the method for preparing a morphology-controllable graphyne-like two-dimensional metal-organic framework material as described in any one of claims 1 to 7.
9. The morphology-controllable graphyne-like two-dimensional metal-organic framework material according to claim 8, characterized in that: The graphyne-like two-dimensional metal organic framework material has a size of 1-20 μm and is a solid hexagonal prism, a hexagonal sheet structure or a hexagonal hollow tube structure.
10. Use of a morphology-controllable graphyne-like two-dimensional metal-organic framework material as claimed in claim 8 or 9 as a catalyst for photocatalytic hydrogen production reaction.
Citation Information
Patent Citations
Method for regulation and control of morphology of amino acid / rare earth coordination polymer by using surfactant
CN104844640A
Method for regulating ZIF-8 crystal morphology by utilizing surfactant
CN107722046A